THE USE OF ACEHNESE-CHAMIC DERIVED LEXICAL ITEMS USED BY ENGLISH DEPARTMENT STUDENTS OF UIN AR-RANIRY - Mustaqim Mustaqim; Zulfadli A. Aziz; Kismullah Abdul Muthalib (Universitas Syiah Kuala, 2020)
The purposes of this study were to analyze the use of Acehnese-Chamic derived lexical items used by young speakers. Besides, it also intended to find out whether there is a language change among younger speakers of Acehnese. The data were gathered at the English Education Department of Teacher Training and Education Faculty of UIN Ar-Raniry University. The informants of this study were English Education students of UIN Ar-Raniry with the average age 20 to 21. There were 12 students involved as the informants of this research. This qualitative study used wordlist interview and interview guide as its method of data collection. The data were analyzed descriptively. The study found that many Acehnese-Chamic derived lexical items were not used by the younger speakers of Acehnese. Furthermore, there was language change which occurred among the younger speakers of Acehnese which consisted of phonological loss in the form of initial consonant dropping, initial syllable dropping and monopthongization. Besides, lexical loss in the form of primary loss and secondary loss are also occurred among younger speakers of Acehnese in this study. Moreover, the younger speakers of Acehnese felt that Acehnese and Indonesian used at home, Indonesian is dominantly used in campus, Indonesian is more convenient than Acehnese, Acehnese used for making jokes, and Acehnese used depending on the partner of speaking were the factors which hinder them from using Acehnese-Chamic derived lexical items.